Assessment of different remote sensing techniques to estimate the CWSI of almond trees using canopy temperature - Álvaro Sánchez-Virosta; Juan Manuel Sánchez; Francisco Montoya; David Gómez-Candón; José González-Piqueras; Antonio Jesús Molina-Medina; Ramón López-Urrea (International Journal of Applied Earth Observations and Geoinformation)
The radiometric temperature of the plants is known to be a good indicator of their level of water stress. The use of thermal cameras on board UAVs allows operational monitoring of the canopy temperature in orchard plantations at the single-tree level. The radiometric processing of the flight data becomes critical in this task to maintain the accuracy provided by field measurements using proximal thermal radiometers. This work focuses on evaluating the Crop Water Stress Index (CWSI) as a good indicator of the plant water status in almond orchards. This study compares the performance of CWSI by three different techniques: i) using proximal high-precision thermal radiometry (CWSI_CIMEL); ii) by UAV thermal flights for canopy temperature assessment (CWSI_UAV) and iii) combining multispectral and thermal data, also by UAV, to run a simplified two-source surface energy balance for the traditional formulation of the CWSI in terms of canopy transpiration (CWSI_STSEB).This study was conducted on two commercials almonds (Prunus dulcis (Mill.) D.A. Webb) orchards located in Albacete (SE Spain), one of them with 3 irrigation treatments (well-watered, moderate water stress, and severe water stress). Periodic measurements of stem water potential (SWP) were carried out around noon throughout 3 experimental campaigns from 2019 to 2021. Canopy temperature measurements were made with a high-precision thermal radiometer, the CIMEL CE312-C2. In addition, six flights were carried out using a DJI-M600 drone equipped with a FLIR Tau2 thermal sensor and a Micasense RedEdge camera. Maps of the CWSI were performed during these dates, showing temporal and spatial variability. The three different techniques showed similar CWSI trends across dates and treatments. When treatments were pooled within the same date, the assessment with SWP measurements showed correlations (R2) of 0.86, 0.68, and 0.70 for CWSI_CIMEL, CWSI_UAV, and CWSI_STSEB, respectively. These results reinforce the potential of accurate measurements of radiometric canopy temperatures using both proximal and remote sensing techniques to reproduce the crop water status in almond orchards. However, this study points to the necessity for accurate sensor calibrations and an appropriate methodology for the treatment of both canopy temperature and meteorological data. Monitoring CWSI serves as an operational tool for the early detection of water deficits in almond trees and meets farmerś needs to improve water use efficiency and optimize irrigation scheduling at the plot level.